Students’ Perception on Using Short Story to Develop Vocabulary at SMP Regina Caeli Cileungsi - Sembiring, Marcelia (JET (Journal of English Teaching), 2022)
Short stories are believed to be a powerful educational tool and play critical roles in EFL classrooms as they provide advantageous authentic learning material, facilitate language development, offer cultural enrichment, and boost personal involvement. This study aimed at describing students' perception of using short stories to develop vocabulary. Employing a cross-sectional survey design, the study was conducted at SMP Regina Caeli Bogor in April 2020 and involved 59 eighth graders Data was collected using an online questionnaire. The findings showed that the participants had a positive perception of using short stories to develop vocabulary. Thus, the majority of students at SMP Regina Caeli Cileungsi viewed the use of a short story as interesting, useful, and easy to develop English vocabulary.